ANALISIS UNSUR-UNSUR SANAD DALAM PENENTUAN KUALITAS HADIS - Ahmad Siddiq Setiawan; Muhammadiyah Amin (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study aims to discuss the analysis of the chain of narration (isnād) in determining the quality of hadiths. The research method used is library research, which involves collecting data from books and various hadith compilations relevant to the topic of discussion. The results and discussion of this research show that analyzing the chain of narration plays a crucial role in determining the quality of a hadith’s sanad (chain of transmission). After analyzing the elements of the sanad, such as the narrators’ names, the forms of transmission (ṣīghah), and the number of narrators, the researcher found that each of these elements requires thorough investigation through various reference works to deepen the analysis of the hadith chain’s condition. The analysis of narrators’ names should be carried out by consulting multiple rijāl al-ḥadīth (biographical) books. Likewise, the analysis of ṣīghah requires examining teacher–student relationships and corroborating them with evidence from the explanations of scholars found in classical works. The analysis of the number of narrators in the sanad demands access to a wide range of sources without limiting the investigation to specific books, in order to trace the length or brevity of the chain. Although determining the quality of a hadith may consider the number of narrators in the chain, further analytical depth is still necessary. This study recommends that hadith scholars and academics further develop this research and apply its framework in future hadith studies.